Self-perception of stigma among epilepsy patients in Malaysia - Rathor, Mohammad Yousuf; Shahar, Mohammad Arif; Omar, Ahmad Marzuki; Mohd Shah, Azarisman Shah; Draman, Che Rosle; Tin, Maw (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
Introduction: Epilepsy remains a stigmatised disease across geographical and temporal boundaries. Very little is known about epileptic stigma (ES) in cross-cultural settings. The aim of this study was to assess the prevalence of perceived stigma and factors associated with it, among patients with epilepsy (PWE) at a tertiary care referral hospital in East Coast of Malaysia. Methods: A cross sectional survey among 132 consenting PWE using pre-tested, semi-structured questionnaire in Malay/English language to assess their knowledge, attitude and practices (KAPs). Results: Among 132 respondents, 51.5% were male and 48.5 % were female. Their age ranged from 14 to 70 years (mean=31.6±13.41). Majority (53.8%) of them were aged 30 years or younger. The median number of years they had epilepsy was 8.0 (IQR 4.0-18.8) years and average duration of seizure prior to seeking medical attention was 1.0 (IQR 0.3 - 4.5) year. Most of them (90.9%) did not know the cause of epilepsy; however nearly all (91.7%) believed that it was a disease of the brain. Higher education level respondents possessed significantly higher KAP scores compared to lower education level respondents (p<0.001). Respondents with good KAP scores believed that epilepsy was not contagious and they observed greater social tolerance. Conclusion: Our study suggests that there is an inverse relationship between knowledge and ES. Self-perceived stigma was more common among our PWE. The results suggest that there is a critical need to enhance epilepsy education amongst the PWE beyond mere seizure control.